Ethical challenges in accessing and providing healthcare for Syrian refugees in Türkiye - BARIŞ, MAİDE; SERT, GÜRKAN; ÖNDER, ORHAN (My University, 2023)
Türkiye hosts approximately 3.6 million Syrian refugees, which accounts for roughly 4.5% of Türkiye\"s population. This places undeniable pressure on public institutions, particularly on healthcare services. The objective of this study is to document the healthcare structure for Syrian refugees and various challenges faced by Syrians when seeking healthcare and to highlight the ethical concerns emerging from those challenges. To achieve this, we conducted a comprehensive review of several qualitative studies and reports conducted by various organizations and institutions, specifically focusing on health or including a dedicated chapter on health issues, published between 2011 and 2023. Following an extensive analysis of the secondary literature, we classified the challenges into three categories: procedural, cultural, and psychosocial. We argue that each of these challenges is linked to overarching medical ethics concerns. Finally, we propose three possible means to mitigate the challenges Syrians experience in accessing and uptake of healthcare services in Türkiye.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sosyal ve Beşeri Bilimler; Felsefe; Sosyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Social Sciences and Humanities; Philosophy; Sociology; Health Sciences; Klinik Tıp (MED); Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Klinik Tıp; Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; FELSEFE; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Clinical Medicine (MED); Arts & Humanities (AHCI); Social Sciences (SOC); CLINICAL MEDICINE; ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; HEALTH CARE SCIENCES & SERVICES; PHILOSOPHY; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Sağlık (sosyal bilimler); Sosyal Bilimler ve Beşeri Bilimler; Sağlık Politikaları; Health (social science); Social Sciences & Humanities; Health Policy; refugee health; refugee healthcare in Türkiye; Syrian conflict; Syrian refugees